Accessibility to the drinking water sources in Burkina Faso: the case study of Toessin and Bonogo villages - Moumouni, Nabaloum; Pounyala, Ouoba Awa; Dapola, Da Evariste Constant (Penerbit Universiti Kebangsaan Malaysia, 2020)
In Africa, accessibility to drinking water is major problem for rural population. This study analyzes accessibility to the drinking water source in two villages in Burkina Faso. Data were obtained from household’s surveys. In total, 221 households have been surveyed. Data analysis method is based on water accessibility of World Health Organization & United Nations Children Fund (2017) and Howard & Bartram (2003) approach. Results show that in Toessin village, more than half of the households have improved service or intermediate access to wells, whereas a small percentage have access to boreholes. Slightly over half of the households have a low service or a minimal access for the same quantities of water and sources. No household falls under the limited service state or does not have access to wells, whereas small number of the families do not have access to boreholes. In the Bonogo village, nearly one third of households have improved service or intermediate access to boreholes and a very small number of household have intermediate access to wells. The majority of the Bonogo household’s access to boreholes fall under the basic service or a minimal access category, whereas accessibility to wells under the same category constitute slightly over half of the household. However, only a very small number of household in Bonogo have a limited service or do not have access at boreholes and wells. Overall, in terms of accessibility to drinking water sources, the majority of households in Toessin falls under the improved service or intermediate/minimal access for wells, whilst in Bonogo, most households fall under the basic service or minimal access to boreholes. It is necessary to dig new boreholes in Toessin in order to improve access to the drinking water.